2017
DOI: 10.1371/journal.pone.0175317
|View full text |Cite
|
Sign up to set email alerts
|

Differential CLE peptide perception by plant receptors implicated from structural and functional analyses of TDIF-TDR interactions

Abstract: Tracheary Element Differentiation Inhibitory Factor (TDIF) belongs to the family of post-translationally modified CLE (CLAVATA3/embryo surrounding region (ESR)-related) peptide hormones that control root growth and define the delicate balance between stem cell proliferation and differentiation in SAM (shoot apical meristem) or RAM (root apical meristem). In Arabidopsis, Tracheary Element Differentiation Inhibitory Factor Receptor (TDR) and its ligand TDIF signaling pathway is involved in the regulation of proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 44 publications
1
25
0
1
Order By: Relevance
“…; Li et al . ). Protophloem development is suppressed by CLE45 and depends on the LRR‐RLK BAM3 (Depuydt et al .…”
Section: Post‐translationally Modified Peptides and Peptide Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…; Li et al . ). Protophloem development is suppressed by CLE45 and depends on the LRR‐RLK BAM3 (Depuydt et al .…”
Section: Post‐translationally Modified Peptides and Peptide Familiesmentioning
confidence: 99%
“…CLE peptides are also involved in vascular development, where they act as negative regulators of stem cell differentiation. CLE41/44 (alias TRACHEARY ELEMENT DIFFERENTIATION INHIBITORY FACTOR; TDIF) promotes procambial proliferation by suppressing xylem differentiation (Hirakawa et al 2008) and lateral root formation (Cho et al 2014) through the LRR-RLK TDR (TDIF RECEPTOR) alias PXY (PHLOEM INTERCA-LETED WITH XYLEM; Fisher & Turner 2007;Hirakawa et al 2008;Zhang et al 2016b;Li et al 2017). Protophloem development is suppressed by CLE45 and depends on the LRR-RLK BAM3 (Depuydt et al 2013).…”
Section: The Clv3 and Cle (Clv3/endosperm Surrounding Region (Esr)-rementioning
confidence: 99%
“…1B ). N-linked glycosylation is quite common in the ectodomains of plant LRRs 50 . Indeed, several N-glycosylation sites have been detected in the LRR ectodomains of FLS2, EFR, and BAK1 receptors that recognize microbe associated molecular patterns (MAMPs) 51 , 52 .…”
Section: Resultsmentioning
confidence: 99%
“…The positively charged patch on the concave side is likely due to the presence of an abundant number of lysine and arginine residues at positions K64, R75, K88, R94, R97, K112, K117, R142, R143, and R150, which are conserved in most of the PRK3 orthologs from Arabidopsis thalian to Cajanus cajan . From the previously published LRR ectodomain structures, it has been demonstrated that the concave surface residues generally interact with other proteins or ligands 50 . Therefore, we can safely suggest that the positively charged surface will provide a favorable interacting surface for negatively charged proteins.…”
Section: Resultsmentioning
confidence: 99%
“…本实验室2015 年 解 析 了 导 管 分 子 分 化 抑 制 因 子 TDIF/CLE44/ CLE41与富亮氨酸重复类受体激酶PXY LRR 复合物的 晶体结构 [34] [35] . 相关的结 果 也 被 另 外 两 个 实 验 室 解 析 出 的 PXY-CLE41 所 验 证 [36,37] . 这一结构不仅为其他功能众多的CLE与受 [38] .…”
Section: 植物Cle家族小肽的识别与受体激活机理unclassified